Thermodynamic Properties of Cryogenic Fluids - Jacobsen, Richard T. (Plenum Press, 2011)
Practicing engineers and scientists will benefit from this book's presentation of the most accurate information on the subject. The equations for fifteen important cryogenic fluids are presented in a basic format, accompanied by pressure-enthalpy and temperature-entropy charts and tables of thermodynamic properties.